2021
DOI: 10.1038/s41598-021-84001-6
|View full text |Cite
|
Sign up to set email alerts
|

A reappraisal of the prevalence of pediatric hypertension through a nationwide database in Taiwan

Abstract: Hypertension in childhood and adolescence is associated with adult cardiovascular morbidity and mortality. However, the reported prevalence of pediatric hypertension varies considerably. We conducted a pioneer nationwide population-based study to investigate the prevalence of hypertension among children and adolescents. Pediatric patients who had been diagnosed with hypertension between 2000 and 2013 were selected from the National Health Insurance Research Database in Taiwan. Other metabolic syndrome-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
1
3
1
Order By: Relevance
“…This study reports that by both guidelines 17.0% and 22.0% of boys and 5.3% and 7.5% of girls have abnormal BP, and the prevalence of HTN is 0.4% and 1.5% among girls and 3.2% and 6.5% of boys in Ukraine. We confirmed that boys are generally 3 times more predisposed to abnormal BP, which is close to the results of other studies [15,18,20]. Sebekova et al, based on survey data from 2543 Slovak students of secondary schools aged from 16 to 23 years, showed that 15% of males and 4% of females presented high normal BP whilst 9% and 1%, respectively, had hypertension [22].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study reports that by both guidelines 17.0% and 22.0% of boys and 5.3% and 7.5% of girls have abnormal BP, and the prevalence of HTN is 0.4% and 1.5% among girls and 3.2% and 6.5% of boys in Ukraine. We confirmed that boys are generally 3 times more predisposed to abnormal BP, which is close to the results of other studies [15,18,20]. Sebekova et al, based on survey data from 2543 Slovak students of secondary schools aged from 16 to 23 years, showed that 15% of males and 4% of females presented high normal BP whilst 9% and 1%, respectively, had hypertension [22].…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of high BP varies widely across worldwide studies (range 0.6-25.1%) performed at different times, in different manners, age groups, and populations of children and adolescents. For instance, the prevalence of prehypertension and hypertension in Lithuanian adolescents aged 12-15 years is 12.8% and 22.2%, respectively [15], in 9-13-yearold Greek schoolchildren it is 14.2% and 23%, respectively [16], in Portuguese children and adolescents aged 4 to 18 years it is 21.6% and 12.8%, respectively [17] and in 10-18-year-old Polish schoolchildren it is 6.6% and 8.9%, respectively [18], while in the US paediatric population HTN has been estimated to affect from 0.1% to 0.3% of children aged 3-17 years [19] and 0.19 to 0.38 per 1000 children in Taiwan [20].…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension may be underestimated in EHR systems when BP is not monitored or when patients are not followed up in the given EHR system. However, our study results suggested that the burden of pediatric hypertension was approximately two-fold higher than that in a population-based study using ICD-9 codes that define hypertension between 2000 and 2013 in Taiwanese youths [27]. These results suggest that pediatric hypertension is underdiagnosed and underestimated in Taiwan.…”
Section: Discussioncontrasting
confidence: 75%
“…This finding is consistent with national data showing that the prevalence of hypertension has been consistently higher in male children and adolescents for over a decade in Taiwan. 50 Also, it has been long evident that the risk for OSA differs by sex. Male sex is a key risk factor for severe adolescent OSA 51 and OSA evolving from childhood to young adulthood.…”
Section: Discussionmentioning
confidence: 99%